2016
DOI: 10.1097/scs.0000000000003077
|View full text |Cite
|
Sign up to set email alerts
|

Can a Specific Computed Tomography-Based Assessment Predict the Ophthalmological Outcome in Pure Orbital Floor Blowout Fractures?

Abstract: The aim of this study was to determine the predictive value of a specific computed tomography (CT)-based assessment for the final functional ophthalmological outcome in pure orbital floor blowout fractures. Data of 34 consecutive patients with pure blowout fractures who had undergone a period of at least 6 months of medical and ophthalmological follow-up were analyzed. The following 3 CT scan-based parameters were included: area ratio of the fractured orbital floor (RF), maximum height of periorbital tissue he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…In 2016, we performed a preliminary study on 34 patients to determine the predictive power of fracture size, IRM displacement, and periorbital tissue herniation. 36 We found fracture size and periorbital tissue herniation to be predictors of enophthalmos and persistent annoying diplopia, respectively. No association could be established between IRM displacement and either enophthalmos or diplopia.…”
Section: E4mentioning
confidence: 69%
See 1 more Smart Citation
“…In 2016, we performed a preliminary study on 34 patients to determine the predictive power of fracture size, IRM displacement, and periorbital tissue herniation. 36 We found fracture size and periorbital tissue herniation to be predictors of enophthalmos and persistent annoying diplopia, respectively. No association could be established between IRM displacement and either enophthalmos or diplopia.…”
Section: E4mentioning
confidence: 69%
“…28,29 Others showed that the position and swelling of the inferior rectus muscle (IRM) in relation to the fracture were associated with persistent diplopia outcomes. [30][31][32][33][34][35][36][37][38][39][40] To date, only a few retrospective studies have reported specifically on the predictive value of the degree of displacement of the IRM into the maxillary sinus as assessed on CT scans for residual diplopia and/or enophthalmos. [30][31][32][33][34][35][36][37][38][39][40] However, no prospective studies have assessed the predictive value of displacement of the IRM into the maxillary sinus in determining the need for surgical treatment in BOFs and/or preoperative diplopia.…”
mentioning
confidence: 99%
“…The fractured area is an important predictor for enophtalmos even in patients undergoing surgery [12]. It has been reported to be a more important predictor for GMP than preoperative enophtalmos [4, 16].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that observable postoperative GMP occurs despite satisfactory surgery poses the question of whether surgical restoration is necessary in patients with minor symptoms or findings. Bruneau et al [12] showed in their study of 34 isolated orbital floor fractures that GMP and diplopia were not resolved with surgery. The final clinical outcome was not better in patients with surgery compared with patients who did not undergo surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation